1976
DOI: 10.1002/bjs.1800630407
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of drainage after cholecystectomy

Abstract: A prospective controlled trial of drainage after cholecystectomy has been carried out. In a consecutive series of 143 patients undergoing cholecystectomy, 50 patients were randomly allocated to a drainage group and a further 50 patients to a non-drainage group. The remaining 43 patients were drained electively because the common bile duct was explored or because of infection or incomplete haemostasis. There was no significant difference in the incidence of wound infection or other complications between the dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 8 publications
3
14
0
1
Order By: Relevance
“…Average age of presentation of cases of cholelithiasis was 44.5 years, comparable to various studies as reported 54, 47 and 45 years by Singh et al (2010), William et al (1972) 13 ; Gordan et al (1976) 14 and Danlel et al (1982) 15 respectively. It means that the disease is most common in the 5 th decade of life.…”
Section: Agesupporting
confidence: 82%
“…Average age of presentation of cases of cholelithiasis was 44.5 years, comparable to various studies as reported 54, 47 and 45 years by Singh et al (2010), William et al (1972) 13 ; Gordan et al (1976) 14 and Danlel et al (1982) 15 respectively. It means that the disease is most common in the 5 th decade of life.…”
Section: Agesupporting
confidence: 82%
“…tThree Staph aureus (1, 1, 3); two Staph albus (0-5, 0-5); two Citrobacter (1, 20); one Acinetobacter (15); one Enterobacter (25). Of the 17 patients who developed wound sepsis, seven discharged pus from which no organism was grown.…”
Section: Resultsmentioning
confidence: 99%
“…Although less relevant in the laparoscopic era, drainage of Morison pouch following cholecystectomy (a clean-contaminated procedure) comprised the standard of care for a century since the procedure was first performed in 1882 [9,10]. Despite the frequency with which it was performed, controversy existed as to whether or not routine post-operative drainage following cholecystectomy was beneficial [10][11][12][13]. Although initial studies focused on the relationship between open drains and post-operative morbidity [11,12,14], as CSDs increased in usage, their effect on morbidity was examined similarly.…”
Section: Intra-abdominalmentioning
confidence: 99%
“…Despite the frequency with which it was performed, controversy existed as to whether or not routine post-operative drainage following cholecystectomy was beneficial [10][11][12][13]. Although initial studies focused on the relationship between open drains and post-operative morbidity [11,12,14], as CSDs increased in usage, their effect on morbidity was examined similarly.…”
Section: Intra-abdominalmentioning
confidence: 99%